2000
DOI: 10.1186/cvm-1-1-031
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the TIMI frame count: implications for future trials

Abstract: Although the TIMI (Thrombolysis In Myocardial Infarction) flow grade classification scheme is widely used to assess angiographic outcomes, it is limited by poor reproducibility and its categoric nature. The corrected TIMI frame count (CTFC) is a simple, more objective continuous variable index of coronary blood flow that can be broadly and inexpensively applied. This measure of the time for dye to traverse a coronary artery is both accurate (highly correlated with Doppler velocity measurements) and precise (re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 21 publications
(30 reference statements)
0
5
0
2
Order By: Relevance
“…with the exception of signi cant increase in TFC with nitrate administration in both healthy and diseased coronary vessels [17]. Reproducibility for prior trials involving manual TFC has been reported as intraobserver reproducibility of 0.75 ± 4.3 frames [18] and 0.91 ± 3.2 frames [19], and correlation between observers of 0.97-0.99 [19], [20]. Here, we report a reproducibility of 1.253 ± 1.814 frames when we randomly reanalyzed a representative 30 of our study's 97 participants' angiographic image series for reproducibility of automatic TFC values for the same angiographic image series, ED frames, and vessel length for a given study participant.…”
Section: Discussionmentioning
confidence: 99%
“…with the exception of signi cant increase in TFC with nitrate administration in both healthy and diseased coronary vessels [17]. Reproducibility for prior trials involving manual TFC has been reported as intraobserver reproducibility of 0.75 ± 4.3 frames [18] and 0.91 ± 3.2 frames [19], and correlation between observers of 0.97-0.99 [19], [20]. Here, we report a reproducibility of 1.253 ± 1.814 frames when we randomly reanalyzed a representative 30 of our study's 97 participants' angiographic image series for reproducibility of automatic TFC values for the same angiographic image series, ED frames, and vessel length for a given study participant.…”
Section: Discussionmentioning
confidence: 99%
“…TIMI flow is currently the method of choice for the evaluation of the coronary flow on a cineangiogram. Be that as it may, this favorable method is not entirely devoid of pitfalls, first and foremost amongst which are its significant interobserver variability and its diagnosis of many patients with different blood flow velocities as normal (TIMI 3 flow) ( 3 ). TFC is a quantitative, reproducible, and objective index of the coronary flow that allows standardization of TIMI flow grades ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The number of frames needed until the contrast media opacify the total length of a vessel from the beginning to the standard distal landmarks is counted ( 2 ). The correlation of this method with the results of doppler has been demonstrated ( 3 ). The well-known TIMI flow assessment, which describes coronary flow as categories of 0 to 3, has some drawbacks.…”
Section: Introductionmentioning
confidence: 96%
“…Выраженность интракоронарного тромбоза обусловлена реактивностью тромбоцитов, активностью плазменного гемостаза и эндогенного фибринолиза (ЭФ), а также Кровоток по ИСА классифицировали с помощью шкалы TIMI Grade Flow [8]. По данным КГ, у 63 пациентов отмечался кровоток по ИСА TIMI 0-1, в то время как у 30 пациентов регистрировался кровоток TIMI 2-3.…”
Section: заключениеunclassified